The branched-chain amino acid transaminase 1 sustains growth of antiestrogen-resistant and ERα-negative breast cancer - Thewes, Verena; Schmidt, Karsten; Kneisel, Niclas; Sinn, Peter; Schneeweiss, Andreas; Okun, Jürgen G.; Lichter, Peter (Oncogene, 2017)
Antiestrogen-resistant and triple-negative breast tumors pose a serious clinical challenge because of limited treatment options. We assessed global gene expression changes in antiestrogen-sensitive compared with antiestrogen-resistant (two tamoxifen resistant and two fulvestrant resistant) MCF-7 breast cancer cell lines. The branched-chain amino acid transaminase 1 (BCAT1), which catalyzes the first step in the breakdown of branched-chain amino acids, was among the most upregulated transcripts in antiestrogen-resistant cells. Elevated BCAT1 expression was confirmed in relapsed tamoxifen-resistant breast tumor specimens. High intratumoral BCAT1 levels were associated with a reduced relapse-free survival in adjuvant tamoxifen-treated patients and overall survival in unselected patients. On a tissue microarray (n=1421), BCAT1 expression was detectable in 58% of unselected primary breast carcinomas and linked to a higher Ki-67 proliferation index, as well as histological grade. Interestingly, BCAT1 was predominantly expressed in estrogen receptor-α-negative/human epidermal growth factor receptor-2-positive (ERα-negative/HER-2-positive) and triple-negative breast cancers in independent patient cohorts. The inverse relationship between BCAT1 and ERα was corroborated in various breast cancer cell lines and pharmacological long-term depletion of ERα induced BCAT1 expression in vitro. Mechanistically, BCAT1 indirectly controlled expression of the cell cycle inhibitor p27Kip1 thereby affecting pRB. Correspondingly, phenotypic analyses using a lentiviral-mediated BCAT1 short hairpin RNA knockdown revealed that BCAT1 sustains proliferation in addition to migration and invasion and that its overexpression enhanced the capacity of antiestrogen-sensitive cells to grow in the presence of antiestrogens. Importantly, silencing of BCAT1 in an orthotopic triple-negative xenograft model resulted in a massive reduction of tumor volume in vivo, supporting our findings that BCAT1 is necessary for the growth of hormone-independent breast tumors.
Gesehen am 17.04.2018